Unusual Intracerebral Hemorrhage Secondary to Delayed Posttraumatic Middle Meningeal Artery Pseudoaneurysm, Successfully Treated by Endovascular N-Butyl Cyanoacrylate Embolization - Mandar G. Waghralkar; Piyush Ojha; Gaurav Goel; Anirban Deep Banerjee; Anshu Mahajan (Indian Journal of Neurosurgery)
Pseudoaneurysm of the middle meningeal artery, presenting as a delayed sequela of trauma, being a rare entity, may sometimes present as an acute intraparenchymal hemorrhage, with a risk of rerupture and mortality. The optimal management in acute settings remains undetermined. We, hereby, report a case of elderly gentleman with a history of a road traffic accident. Noncontrast computed tomography (NCCT) brain was reported to have left parietal hemorrhagic contusion without any mass effect. The patient was managed conservatively without any major neurological deficits. After 7 months, the patient presented with severe headache, altered sensorium, and right hemiparesis. NCCT brain showed acute left thalamocapsular hemorrhage with minimal subarachnoid hemorrhage with associated mass effect and impending herniation. Considering the fall in patient's baseline Glasgow comma scale response, pupillary asymmetry, and CT findings, immediate decompression and hematoma evacuation were advised. In view of atypical morphology, the patient was planned for urgent digital subtraction angiography prior to the surgery to rule out the ruptured aneurysm or pial arterio-venous fistula. Selective angiography of the left external carotid artery demonstrated a dissecting pseudoaneurysm feeding from the middle meningeal artery (MMA), which was embolized using n-butyl cyanoacrylate (NBCA). Postprocedure DynaCT revealed the left temporal bone fracture, indicating this pseudoaneurysm to be most likely posttraumatic delayed sequelae. Postembolization, the patient underwent surgical decompression and excision of hematoma. Patient's neurological status gradually improved and was discharged with the minimal deficit. Our case highlights the importance of awareness of the posttraumatic MMA pseudoaneurysm as an uncommon but treatable entity, which can be easily diagnosed using cerebral angiography and amenable to safe and effective endovascular embolization using NBCA.